Розподіл оксиду титану в нанокомпозитах системи SiO2–TiO2 - Горбик, П.П.; Гунько, В.М.; Зарко, В.І.; Міщук, О.О.; Співак, О.А.; Чуйко, О.О. (Видавничий дім "Академперіодика" НАН України, 2007)
The researches of the element structure of surface layers are carried out by methods of electronic raster microscopy and Auger-spectroscopy. The influence of dioxide titanium on structure surface layers of the system SiO2–TiO2 is investigated. A connection between the surface concentration of the second oxide phase in titanium silica or aluminum silica and their zeta-potential is investigated.